Perancangan dan Pelatihan Sistem Informasi Administrasi Surat di Kalurahan Kedungkeris Nglipar Gunung Kidul - Indrayana, Masrul (Universitas Widya Mataram, 2025)
The Kedungkeris Village is one of the governmental institutions located in the Nglipar District, Gunung Kidul Regency. Kedungkeris Village has already implemented a Village Information System (Sistem Informasi Desa or SID). SID is a platform developed by the Ministry of Villages, Development of Disadvantaged Regions, and Transmigration (Kemendes PDTT) to help village governments manage data and information that supports data-based or evidence-based planning and budgeting. SID serves as a medium for transparency, allowing public access to village information. However, the SID utilized by Kedungkeris Village does not yet support operational activities related to other village administrative management, such as recording incoming and outgoing correspondence. These records are still manually maintained in a ledger. A Village Correspondence Administrative Information System model for Kedungkeris Village, Nglipar, Gunung Kidul, Yogyakarta, has been successfully developed using MS Access. This information system has been effectively utilized by the village administration with satisfactory results.